The Impact of IQ and EQ on Students’ Psychological Well-being: An Empirical Study on University Students - Zahra, Gulle; Ahmad, Nawaz; Kaddour, Amira (Pakistan Business Review, 2024)
The study attempts to gauge empirically the impact of Intelligence Quotient (IQ) and Emotional Quotient (EQ) on the student’s psychological well-being. The population comprises university students. Data is collected through convenience sampling via a five-point Likert scale questionnaire. The total number of respondents in the survey were 200, which consisted of 109 males and 91 females. IQ and EQ are the independent variables, whereas psychological well-being is the dependent variable, with the moderating variables of Age and Gender. The study's findings reveal that IQ and EQ positively impact psychological well-being and are significant at a 99 per cent confidence interval (p
Keywords: IQ; EQ; psychological well-being